Five years of social security reform in the UK - Mike Brewer; Tom Clark; Matthew Wakefield (Institute for Fiscal Studies (IFS), 2002)
The current Labour Government was elected in 1997 with few specific social security proposals. This paper argues that after five years, consistent trends in social security policy have emerged: there is a willingness to increase benefits; a “work-first” focus; increasing centrality for benefits that relate to `need', which has involved expanded means-testing; a downgrading of contributory benefits; and, a desire to reduce poverty by redistributing to particular demographic groups. Many of these characteristics of Labour policy, such as the size of caseloads or aggregate expenditure, are yet to show up in various aggregate data, and we argue that this is probably due to various counter-balancing socio-economic changes since 1997. Looking forward, we discuss what the introduction of new forms of means-test might achieve. We also suggest that it might be considered odd that Labour has left Housing Benefit and Council Tax Benefit unreformed, especially since a good chance to reform them without significant cost or low-income losers, has been missed.
Keywords: D31; I30; H24; H53; H55; 330; Soziale Sicherung; Sozialreform; Ökonomischer Anreiz; Großbritannien